A ASSOCIATION OF BODY MASS INDEX WITH HEALTH RELATED QUALITY OF LIFE IN ELEMENTERY SCHOOL AGE CHILDREN - Edwin Timoti Japanto (Jurnal Kedokteran Methodist, 2025)
Background : Nutrition problems in school-age children still occur in Indonesia and associated with a decrease in quality of life in children. School-age children are vulnerable to physical, emotional, social and school problems. Objective : To find out the relation between Body Mass Index (BMI) with Health Related Quality of Life (HRQOL) Methods : This cross-sectional study measured BMI with body weight and height using the z-score method and measuring quality of life (QOL) in children using a generic core scale Pediatric Quality of Life Inventory (PedsQL) 4.0. This research was conducted on school-age children 8-12 years old at Budya Wacana Yogyakarta Elementary school in 2018. Results: The statistical test on 143 respondents using chi square test for bivariate and logistic regression for multivariate. The bivariate test results showed a significant relationship between BMI and quality of life in children (p = 0.013), especially in the domain of emotional function (p = 0.015) and social function (p = 0.036). There was a significant relationship between age and quality of life (p = 0.002) and between sex with quality of life (p = 0.037). There was no significant relationship between disease and quality of life (p = 0.975). The results of multivariate analysis showed BMI (p = 0.001) had a greater correlation between quality of life in children than age (p = 0.03) or sex (p = 0.076). Conclusion : There is a significant relationship between BMI and quality of life in school-aged children at SD Budya Wacana Yogyakarta